VP2RQ: Efficient verifiable privacy-preserving range query processing in two-tiered wireless sensor networks. (November 2016) - Dai, Hua; Ye, Qingqun; Yi, Xun; He, Ruiliang; Yang, Geng; Pan, Jinji
In the field of wireless sensor networks, the secure range query technique is a challenging issue. In two-tiered wireless sensor networks, a verifiable privacy-preserving range query processing method is proposed that is based on bucket partition, information identity authentication, and check-code fusion. During the data collection process, each sensor node puts its collected data into buckets according to the bucket partition strategy, encrypts the non-empty buckets, generates the check-codes for the empty buckets, and fuses them. Then, the check-codes and the encrypted buckets are submitted to the parent node until they reach the storage node. During query processing, the base station converts the queried range into the interested bucket tag set and sends it to the storage node. The storage node determines the candidate-encrypted buckets, generates the check-code through code fusion, and sends them to the base station. The base station obtains query results and verifies the completeness of the result with the check-code. Both the theoretical analysis and experimental results show that verifiable privacy-preserving range query is capable of protecting the privacy sensor data, query result, and query range, which also supports the completeness verification of the query result. Compared to existing methods, verifiable privacy-preserving range query performs better on communication cost.